Nanofiber Organic Semiconductors: The Effects of Nanosize on the Electrical Charge Transport and Optical Properties of Bulk Polyanilines - Yakuphanoğlu, Fahrettin; Mehrotra, R.; Gupta, A.; Munoz, M. (Wiley, 2009)
The electrical transport, optical, and microstructural properties of bulk polyaniline (PANI) and nano-PANIs were investigated. A field emission scanning electron microscopy (SEM) image of bulk PANI showed macroscopic and aggregated granular particles. A SEM image of the nanostructured PANI showed the formation of one-dimensional nano/microstructures. The formation of nanofibers was observed from the transmission electron microscopy image. The electrical conductivities of the bulk and nanostructured PANIs increased with increasing temperature, which indicated semiconductor behavior. The electrical conductivities of the bulk and nanostructured PANIs at room temperature were found to be 2.12 x 10(-5) and 1.80 x 10(-2) S/cm, respectively. The electrical conductivity of the nanostructured PANI was about 850 times higher than that of the bulk PANI. The obtained band gaps of the bulk and nanostructured PANIs were determined from diffuse reflectance measurements and were found to be 3.27 and 2.41 eV, respectively. The refractive index of the PANI samples changed from 1.3 to 1.61. The obtained results indicate that the electrical and optical properties of the PANI were inherently dependent on the nanostructure. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 114: 794-799, 2009
Keywords: activation energy; charge transport